GENETIC ASPECTS OF INFERTILITY IN ENDOMETRIOSIS - PAKHOMOVA, J.E.; KARAMANYAN, A.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Endometriosis is a common chronic systemic pathology manifested by the growth of endometrium-like tissue outside the uterus with dysmenorrhea, dyspareunia and infertility. 95 women 21-43 years old with ovarian endometriosis of III-IV stages and endometriosis associated infertility (n=42 - 44,21%), as well as with other forms of infertility (n=53 - 55,79%) were examined to determine the association between rs6165 and rs6166 genotypes of FIGLA gene and the risk of infertility in women with endometriosis and other forms of infertility. Decreased AMH level, increased FSH and LH, as well as certain rs6165 and rs6166 genotypes allow predicting the risk of decreased ovarian reserve and the effectiveness of therapy.